Ginger (Kaempferia galanga L) Supplementation to Shorten Broiler Production Period - Muhammad, Z; Nataamijaya, AG (ANIMAL PRODUCTION, 2006)
Consumers increasingly prefer to buy broiler weighted approximately one kg.  In this study broiler chicks were feed with commercial diet, which composed from corn, soybean, fishmeal, rice bran, dicalcium phosphate, vitamins minerals mixture (premix) and palm oil. The diet contained approximately 20.33 % of crude protein and 3100 Kcal/kg of metabolizable energy.  The ginger meal was mixed into the diet according to the treatments i.e P1 (0 %), P2 (0.02%), P3 (0.04 %), P4 (0.08 %) and P5 (0.16 %). The results showed that the total feed intake of P5 (1,808.4 g) and P2 (1,846.5 g) was significantly (P<0.05) less than those of P1 (1,966.5 g). Birds of P5 achieved one kg body weight within 26 days, P2 (27 days) and P3 (27 days) was significantly (P<0.05) less than those compared with birds of P4 (29 hari) and P1 (30 hari). The feed conversion of P5 (1.81) was also better than (P<0.05) that of P1 (1.97), while the Income over Feed and Chick Cost was Rp 1,658.78 (P5); Rp 1,568.06 (P2); Rp 1,426.54 (P3);   Rp 1,280.45 (P1) and Rp 1,195.95 (P4). (Animal Production 8(1): 59-63 (2006) Key Words : Kaempferia galanga L, Broiler